Cost-Effectiveness Analysis of Direct Oral Anticoagulants Vs. Vitamin K Antagonists in the Elderly With Atrial Fibrillation: Insights From the Evidence in a Real-World Setting - Wu, Yue; Zhang, Chi; Gu, Zhi-Chun (Frontiers in Cardiovascular Medicine, 2021)
Background: In the clinical setting, the economic benefits of direct oral anticoagulants (DOACs) in elderly patients with atrial fibrillation (AF) remain unclear. This study aimed to estimate and compare the cost-effectiveness of DOACs and vitamin K antagonists in preventing stroke among AF patients aged > 75 years in real-world practice. Methods: A Markov model with a 10-year span was constructed to estimate the long-term clinical and economic outcomes among AF patients aged > 75 years treated with DOACs and warfarin. The study was populated with a hypothetical cohort of 10,000 AF patients aged > 75 years. Probabilities of clinical outcomes were obtained from the pooled observational studies, comparing DOACs with VKAs. Other model inputs, including the utilities and the costs, were all estimated from public sources and the published literature. The costs, quality-adjusted life-years (QAYLs), and incremental cost-effectiveness ratios (ICER) were estimated for each treatment strategy. Results: Compared to warfarin, DOACs were associated with a gain of 0.36 quality-adjusted life-year (QALY) at an additional cost of $15,234.65, resulting in an incremental cost-effectiveness ratio (ICER) of $42,318.47 per QALY. Sensitivity analysis revealed that the ICER was sensitive to the cost of DOACs. DOACs also shifted from dominating to dominated status When their annual costs of DOACs were over $3,802.84 or the risk ratio of death compared to warfarin was over 1.077%/year. Probabilistic sensitivity analysis (PSA) suggested that DOACs had a 53.83% and 90.7% probability of being cost-effective when the willingness-to-pay threshold was set at $50,000 and $100,000, respectively. Among all the four individual DOACs, edoxaban treatment was revealed as the preferred treatment strategy for the AF patients aged over 75 years by yielding the most significant health gain with the relatively low total cost. Conclusions: Despite the high risk for major bleeding in elderly patients with AF, DOACs are more cost-effective treatment options than warfarin in real-world practice. Edoxaban was the preferred treatment strategy among four kinds of DOACs for AF patients aged over 75 years. Furthermore, beyond their safety profiles, the treatment benefits of DOACs assumed greater relevance and importance in older adults.